Global research trends on macrophage polarization in osteoarthritis: a bibliometric analysis - Bamahel, Abdulaziz S.; Liu, Jia; Zhang, Zhuoyu; Deng, Yizhuo; Xue, Chaoyou; Sun, Xun; Wu, Wei; Bi, Sheng; Zubair, Nadeem; Nie, Guangchen; Xu, Hui (Frontiers in Immunology, 2025)
BackgroundOsteoarthritis, a common degenerative osteochondral disease, has a close relationship between its mechanism of Macrophage polarization. However, there are relatively few relevant studies in this field, and a more mature research system has not yet been formed.MethodsA bibliometric analysis was conducted using the Scopus and WoSCC databases to retrieve articles related to macrophages in OA published from 2013 to 2023. A total of 2,122 articles were analyzed for publication year, contributing countries, institutions, authors, journals, and keywords. VOSviewer software was used for co-authorship, co-citation, co-occurrence, and network visualization. Emerging research subtopics were also identified and reviewed.ResultsThe annual publication output showed a consistent upward trend. China led in the number of publications (623), with China Medical University contributing the most at the institutional level (41 articles). In contrast, the USA had the highest citation count (24,692), and Rush University Medical Center was the most cited institution (902 citations). Frontiers Immunology published the most articles (110), while Osteoarthritis and Cartilage received the highest number of citations (4,995). Chih-Hsin Tang was the most prolific author (16 publications), and Christin M. Lepus was the most frequently co-cited (2,085 citations). The most frequently occurring keywords included “osteoarthritis,” “metabolism,” “macrophage,” and “inflammation.” Researchers formed tightly connected teams with overlapping research themes.ConclusionThis study provides a comprehensive overview of global research on macrophages in OA, highlighting key contributors, journals, and emerging trends. Keyword cluster analysis identified future research directions, including metabolic reprogramming, macrophage polarization, and immune-modulation strategies. Greater standardization in research frameworks and enhanced international collaboration are needed to improve translational impact.